Government Effectiveness Moderation On The Effect Of Per Capita Income And Exchange Rate On Goods And Services Tax Revenue In East Asia And Pacific - Wahyuni, Desak Ari Gita; Wijaya, Suparna (WIM Solusi Prima, 2024)
Taxes have been known as the main source of revenue in every country. Tax on Goods and Services is a clear example of how tax revenue can contribute as a source of government revenue. This type of tax has been implemented in more than 143 countries in the world under the name Goods and Services Tax (GST) or Value Added Tax (VAT), including developed and developing countries which are members of the East Asia and Pacific region. Over the past few years, the issue of GST has become a hot topic of discussion as an approach in fiscal policy to reduce the budget deficit. New challenges and risks arose in line with the efforts of policy makers to maintain and accelerate economic growth in the East Asia and Pacific region. Deglobalization, population aging, and climate change overshadow the prospects for economic growth in this region, which has initially developed rapidly through trade. This research contributes to presenting the results of empirical literature regarding the determinants of tax revenue on goods and services in 12 countries that are members of the East Asia and Pacific region during the 2010-2019 period. Through a quantitative approach and panel data regression analysis method, the results show that the dependent variable GST can be explained by the independent variables consisting of Per Capita Income (PCI) and Exchange Rate (EXCH) of 56.42%. Per Capita Income, Exchange Rate has a positive and significant effect on Goods and Services Tax revenue. Meanwhile, moderation by the Government Effectiveness variable weakens the influence of the two independent variables so that the PCI and EXCH coefficient values become negative. This study also uses the variable Service Sector Contribution to GDP (SERV) as a control variable.